Loving Teacher and Grateful Student: Letters of A. A. Dmitrievsky to K. S. Kekelidze, 1906–1929 - Sergey Yu. Akishin (Вестник Екатеринбургской духовной семинарии, 2025)
The proposed material presents the letters of the outstanding Russian liturgist A. A. Dmitrievsky to his former student at the Kiev Theological Academy, Academician of the Georgian Academy of Sciences K. S. Kekelidze. The introductory article gives brief biographical sketches of the correspondents, characterizes the dynamics of the correspondence and the main topics covered in it; one letter is suggested to be dated by the year 1929, although the scholar himself indicates different year of its writing. Special attention is paid to the description of the source potential of the letters and the systematization of the new information concerning the biography of A. A. Dmitrievsky in 1906–1929: the pre-revolutionary decade of the scientist’s life in St. Petersburg/Petrograd; his life in Astrakhan in 1919–1923; and his return to Petrograd, where the scientist actually had to resettle. In connection with the Leningrad period of A. A. Dmitrievsky’s life, discussed are his teaching and scientific activity, peculiarities of his everyday life and financial situation, as well as his trips outside Leningrad, etc.